Imaging features of osteomyelitis of the jaws with different diagnostic methods. A review - Díaz-Castellón, Dirce Fernanda (2021)
Osteomyelitis of the jaws (OM) is an infectious pathology involving the bone marrow. It is due to various etiologies, the main one being odontogenic. The diagnosis of OM is a challenge for dentists, who must rely on clinical and imaging examinations. Panoramic radiography is the most frequently used imaging test, but it has some limitations that have improved with the incorporation of new imaging methods such as computed tomography, cone beam computed tomography, magnetic resonance imaging, and bone scintigraphy with radionuclides. The purpose of this review was to describe the imaging characteristics of OM of the jaws according to the radiological diagnostic methods available in the literature in order to provide radiologist with greater knowledge and improve reporting in daily practice.